Analysis of The Character Profile of a Pancasila Student in the Implementation of Lesson Study Through Sharing and Jumping Task SMAIT Harapan Umat Karawang - Ratnasari, Ratnasari; Widiyanti, Anik (Universitas Riau, 2024)
Students at SMAIT Harapan Umat was that the level of critical thinking of students was still low, which can be seen from the activeness of asking questions during learning, the inactivity of students during discussions. The purpose of the study was to determine the influence of lesson study in improving critical thinking through sharing tasks and jumping tasks for students of SMA IT Harapan Umat. The research method used in this study is a qualitative descriptive research method. The results of the study show that it has a positive impact on teachers, students, schools, has the effectiveness of other people's results and responses, the effectiveness of learning using sharing tasks and jumping tasks, the effectiveness of Learning Reflection in Lesson Study Improving the Quality and Collaboration of Teachers. The conclusion of the study shows that overall, activities to improve critical thinking skills through Sharing Task and Jumping Task learning in the Lesson Study of SMAIT Harapan Umat have a positive impact.